Prototype of multifunctional transmitter with Rejection of disturbances - Holman Montiel Ariza; Fernando Martínez Santa; Fredy H. Martínez S. (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The industrial instruments found in the different industrial processes allow supervisory and control actions to be carried out. These elements are usually composed of an electronic circuit, which varies according to the specifications given by the manufacturer. Another factor that influences the design of a circuit for elements of this type is cost, since, at a lower cost, electronic elements are susceptible to fail for reasons such as electric fields, motor interference or environmental conditions. This problem limits the operation of the instrument and reduces its useful life, which causes unnecessary stops of the automated processes increasing the cost of producing a product. Some partial solutions to this problem have been obtained by means of the implementation of additional circuits such as protections or filters, although the number of unexpected stops of the process is reduced, even this type of failures occur. This paper proposes an alternative solution to the problem through a low cost prototype, which has a mechanism for rejection of disturbances that increases the accuracy and precision of an instrument compared to the low-cost instrument technology developed so far.